2019
DOI: 10.4000/anthropodev.791
|View full text |Cite
|
Sign up to set email alerts
|

Socialisation sexuelle des jeunes issus des migrations subsahariennes en Suisse

Abstract: Comme d'autres pays européens, la Suisse est confrontée à des changements liés aux flux migratoires concernant tout particulièrement la jeunesse. Cet article s'intéresse aux jeunes issu•es des migrations subsahariennes (première et deuxième génération) vivant en Suisse. Basé sur une recherche qualitative, cet article porte sur la socialisation sexuelle, à savoir les dynamiques d'entrée dans la sexualité, et met en lumière les comportements sexuels ainsi que la gestion des différences culturelles et les tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The latter approach may be particularly fruitful, as it suggests possible intervention strategies, especially in the areas of social work and health. Examining the sexual socialisation of women who have undergone FGM/C allows us to analyse the content of the messages transmitted, the ways and styles of communication, as well as the agents and the places of socialisation [75]. Such an approach brings to light the knowledge and understanding acquired, the beliefs and the ideas received from family and friends, institutions, and the media.…”
Section: Framing and Naming Pleasures And Desires In Postcolonial Stu...mentioning
confidence: 99%
“…The latter approach may be particularly fruitful, as it suggests possible intervention strategies, especially in the areas of social work and health. Examining the sexual socialisation of women who have undergone FGM/C allows us to analyse the content of the messages transmitted, the ways and styles of communication, as well as the agents and the places of socialisation [75]. Such an approach brings to light the knowledge and understanding acquired, the beliefs and the ideas received from family and friends, institutions, and the media.…”
Section: Framing and Naming Pleasures And Desires In Postcolonial Stu...mentioning
confidence: 99%
“…As for parents, they tend to avoid the topic for fear of "encouraging" youth sexual activity (Sulstarova et al, 2019). Accordingly, families consistently avoid conversations about sexuality under the terms of a tacit agreement acknowledging sex as a taboo subject that should only be addressed "in secret" (Villani et al, 2019a). Studies have also found that firstgeneration migrant youth in Switzerland lack knowledge of sexual rights and available sexual health services (Campisi et al, 2017;Mileti et al, 2019).…”
Section: Shortcomings In Responses To Fgm/cmentioning
confidence: 99%